Expression of estrogen and progesterone receptors in astrocytomas: a literature review - Cléciton Braga Tavares; Francisca das Chagas Sheyla Almeida Gomes-Braga; Danylo Rafhael Costa-Silva; Carla Solange Escórcio-Dourado; Umbelina Soares Borges; Airton Mendes Conde-Junior; Maria da Conceição Barros-Oliveira; Emerson Brandão Sousa; Lorena da Rocha Barros; Luana Mota Martins; Gil Facina; Benedito Borges da-Silva (Clinics)
Gliomas are the most common type of primary central nervous system neoplasm. Astrocytomas are the most prevalent type of glioma and these tumors may be influenced by sex steroid hormones. A literature review for the presence of estrogen and progesterone receptors in astrocytomas was conducted in the PubMed database using the following MeSH terms: “estrogen receptor beta” OR “estrogen receptor alpha” OR “estrogen receptor antagonists” OR “progesterone receptors” OR “astrocytoma” OR “glioma” OR “glioblastoma”. Among the 111 articles identified, 13 studies met our inclusion criteria. The majority of reports showed the presence of estrogen and progesterone receptors in astrocytomas. Overall, higher tumor grades were associated with decreased estrogen receptor expression and increased progesterone receptor expression.